Space control and goal shot efficiency in elite water polo - Hohmann, A.; Hochstein, S.; Hohenstein, D. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Shooting is one of the most important performance prerequisites in water polo (Alcaraz, Abraldes, Ferragut et al., 2012). The subject of this study was the throwing behaviour of the world class players under competition match conditions during the final "World Cup Water Polo" tournament 2018 in Berlin. On the basis of the dynamical systems approach, the goal shot has to be interpreted as the result of a macroscopic interpersonal coordination of the attackers in relation to the interpersonal coordination of the defenders. An important key performance indicator describing the macroscopic formations of the players as agents in a complex adaptive system is the space control in front of the goal (Headrick, Davids, Renshaw et al., 2012).